Durability of Concrete Based on the Remaining Life of the Building Case Study: Reinforced Concrete in Klaten District - Widodo, Slamet; Aski Safarizki, Hendramawat; Marwahyudi, Marwahyudi (Universitas Ibn Khaldun Bogor, 2022)
Concrete durability is the ability of concrete to last as it was originally planned, in the structure of a building can be defined as the ability to maintain function, stability and aesthetics due to environmental influences so as not to incur large maintenance and repair costs during the planned service life. The durability aspect is very important, especially for infrastructure that has a fairly long service life. Building life is the period or time during which a structure is required to continue to function as planned. In building structures whose construction has been completed, both new and old buildings, specific data related to the quality of the concrete and the planned age of the building is quite difficult to obtain, this is because the influence during the implementation of construction is also not good in governance. documentation, both technical documents and other non-technical documents, therefore it is necessary to have a sufficiently representative tool to test the concrete quality of a building that has been completed to comply with the quality of the built concrete.